2016
DOI: 10.4306/pi.2016.13.1.89
|View full text |Cite
|
Sign up to set email alerts
|

Parameters of Calcium Metabolism Fluctuated during Initiation or Changing of Antipsychotic Drugs

Abstract: ObjectiveSerum parameters of calcium homeostasis were measured based on previously published evidence linking osteoporotic fractures and/or bone/mineral loss with antipsychotics.MethodsProspective, four-week, time-series trial was conducted and study population consisted of patients of both genders, aged 35-85 years, admitted within the routine practice, with acute psychotic symptoms, to whom an antipsychotic drug was either introduced or substituted. Serial measurements of serum calcium, phosphorous, magnesiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
(56 reference statements)
1
9
0
Order By: Relevance
“…Although no significant differences were found between patients taking psychotropic medication and those who were not, these factors remain of clinical concern with respect to bone health. A recent small-scale prospective study found that antipsychotics may inhibit vitamin D-metabolising enzymes, thereby causing a reduction in both calcium and 25OHD levels 10 . This association is of particular concern given the known link between antipsychotics and osteoporosis risk via raised prolactin levels 11 …”
Section: Discussionmentioning
confidence: 99%
“…Although no significant differences were found between patients taking psychotropic medication and those who were not, these factors remain of clinical concern with respect to bone health. A recent small-scale prospective study found that antipsychotics may inhibit vitamin D-metabolising enzymes, thereby causing a reduction in both calcium and 25OHD levels 10 . This association is of particular concern given the known link between antipsychotics and osteoporosis risk via raised prolactin levels 11 …”
Section: Discussionmentioning
confidence: 99%
“…This result is in line with another study conducted by Lee et al in 2010 in South Korea, which also investigated factors related to bone metabolism, including plasma calcium level between those receiving 1 mg risperidone and 2.5 mg of olanzapine. They found a significant decrease of bone density in schizophrenic patients prescribed with risperidone and olanzapine (p < 0.05), which is correlated to baseline calcium level [8].…”
Section: Discussionmentioning
confidence: 95%
“…In addition to the osteoporosis process, the increased risk of fracture is well documented in treated patients with severe mental disorders. The decrease in calcium levels with antipsychotic therapy may be caused by several mechanisms, including the excretion mechanism in the kidneys, a condition where there is an increase in the excretion of calcium in the urine, and vice versa when there is low absorption of calcium [8].…”
Section: Introductionmentioning
confidence: 99%
“…Sample size calculation was powered with  and  error 0.05 and 0.2, respectively, considering the decrease of 5% of serum calcemia (primary outcome variable) in final blood sample from baseline calcemia of 2.40 mmol/L (standard deviation 0.16 mmol/L) as statistically significant, for paired, two-tailed, one-sample analysis. We based calculation on previous research in the topic but concerning antipsychotic treatment as we consider available data of primary endpoint from studies, which investigated antidepressants in the similar setting to be scarce and unreliable 17 . The initial computed sample size was increased for a half, in order to counteract possible non-parametric distribution and missing data, giving the study group of at least 25 subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, sedatives increase fracture risk mainly due to gait disturbances and antipsychotics induce hyperprolactinemia and hypogonadism predisposing patients to osteoporosis. In fact, the fracture risk in people taking antipsychotic drugs had much more magnitude than in patients taking antidepressants [34][35][36] ; moreover, they could significantly disturb calcemia in the notable number of patients, manly toward low levels 17 . Therefore, if anxiolytics and antipsychotics used by patients in our study did influence bone mineral homeostasis and their serum levels, the aggregate resultant would either facilitate or counteract presumed action of antidepressants.…”
Section: Discussionmentioning
confidence: 99%